Indução de resistência a Pratylenchus brachyurus em soja por óleo essencial de Melaleuca alternifolia - Faria, Vanessa de Oliveira (2024)
Worldwide, soybean is a crop of extreme importance, with Brazil being the largest producer of this grain. Even with productivity increasing year by year, there is still much to advance, especially in nematode management. The root lesion nematode Pratylenchus brachyurus is the second most important pest in this crop due to the difficulty of control and the limited effectiveness of management practices, which primarily involve chemical control. This study aims to evaluate the use of Melaleuca alternifolia essential oil as an alternative method to induce resistance in soybean crops against P. brachyurus. The experiment was conducted in a randomized block design in a greenhouse, with five replications. The treatments consisted of concentrations of 0, 500, 1000, 1500, 2000, and 2500 L L-1 of Melaleuca alternifolia essential oil, with 0 concentration serving as the control, using only distilled water with 0.5% neutral detergent. The treatments were applied through foliar sprays at the V2 phenological stage, followed by inoculation of 500 P. brachyurus individuals per pot three days later. After 60 days of inoculation, agronomic variables (height, fresh and dry shoot mass, and fresh root mass) and nematological variables (number of nematodes and eggs per gram of root) were evaluated. The second assay was conducted with the concentration showing the best performance in the first assay, aiming to assess the activation of plant defense enzymes phenylalanine ammonia-lyase, polyphenol oxidase, peroxidase, and catalase. The analysis was performed at three time points: on the day of inoculation (3 days after treatment), and 9 and 12 days after treatment. There were used two control treatments: one inoculated and untreated, and an absolute control (neither treated nor inoculated). The activity of defense enzymes was determined spectrophotometrically using a protein extract obtained from soybean roots. Analysis of variance and mean comparison were conducted using Tukey's test at a 5% probability level. Melaleuca alternifolia essential oil demonstrated potential for controlling P. brachyurus in soybean and induced resistance through catalase enzyme activation.